Decreased gray matter volume in the left middle temporal gyrus as a candidate biomarker for schizophrenia: A study of drug naive, first-episode schizophrenia patients and unaffected siblings - Guo, Wenbin; Hu, Maorong; Fan, Xiaoduo; Liu, Feng; Wu, Renrong; Chen, Jindong; Guo, Xiaofeng; Xiao, Changqing; Quan, Meina; Chen, Huafu; Zhai, Jinguo; Zhao, Jingping (Schizophrenia research, 2014)
Studies have shown that patients with schizophrenia and their siblings share decreased gray matter (GM) volumes in certain brain regions, which may represent candidate endophenotypes of schizophrenia. However, the specificity and utility of these possible endophenotypes in relation to schizophrenia remain unclear. Twenty drug-naive, first-episode schizophrenia patients and 20 first-degree unaffected siblings from the same families as the patients (USS group), a separate group of 25 first-degree unaffected siblings of schizophrenia patients from other families (USO group), and 43 healthy controls were recruited. Voxel-based morphometry (VBM) was used to analyze structural imaging data. The VBM analysis showed a significant difference in GM volume between the combined sibling group and the control group in the left middle temporal gyrus (MTG). Group comparison showed that the patients, the USS, and the USO had significantly decreased GM volume of the left MTG compared with the controls; such a difference did not exist among the patients and the two sibling groups. A receiver operating characteristic curve (ROC curve) analysis showed good predictive value of the mean cluster volume in the left MTG to distinguish patients, USS, and USO from healthy controls. There were no significant correlations between the mean cluster volume in the left MTG and clinical variables in the patients. The GM volume decrease of the left MTG may be utilized as a candidate biomarker for schizophrenia. The novel design of including a USO group in our study enhances both the specificity and the heritability of the biomarker identified.